2020
DOI: 10.1161/jaha.119.015611
|View full text |Cite
|
Sign up to set email alerts
|

Binge Alcohol Exposure in Adolescence Impairs Normal Heart Growth

Abstract: Background Approximately 1 in 6 adolescents report regular binge alcohol consumption, and we hypothesize it affects heart growth during this period. Methods and Results Adolescent, genetically diverse, male Wistar rats were gavaged with water or ethanol once per day for 6 days. In vivo structure and function were assessed before and after exposure. Binge alcohol exposure in adolescence significantly impaired normal cardiac growth but did not affect whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Abstinence restored cardiac function back to a control level, and in some measures, exceeded control levels. A recent study showed that cardiac growth can be compromised by alcohol consumption in adolescent Wistar rats [35], which is consistent with our findings, though our mice were already in early adulthood. It is possible that alcohol consumption delayed the growth of their hearts, which rebounded after abstinence.…”
Section: Discussionsupporting
confidence: 94%
“…Abstinence restored cardiac function back to a control level, and in some measures, exceeded control levels. A recent study showed that cardiac growth can be compromised by alcohol consumption in adolescent Wistar rats [35], which is consistent with our findings, though our mice were already in early adulthood. It is possible that alcohol consumption delayed the growth of their hearts, which rebounded after abstinence.…”
Section: Discussionsupporting
confidence: 94%
“…Alcohol permeability is further implicated in the disruption of signalling processes, activation of apoptosis, and the loss of heart contraction [ 7 , 9 ]. Even acute alcohol exposure has been demonstrated to elicit haemodynamic changes (cardiac stress) leading to the enlargement of cardiomyocytes [ 7 , 33 , 36 ]. However, it must be noted that myocardial hypertrophy (which causes the thickening of the ventricular wall) may occur at the early stages of alcohol damage as a compensatory mechanism for the sarcoplasmic reticular dysfunction (arising from the effect of alcohol) [ 8 , 9 , 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A hindered repair mechanism promotes myocardial fibrosis [ 9 ] disrupting myocardial remodelling which is an essential contributor to the repair of ventricular wall damage [ 10 , 38 ]. The failure of remodelling after ventricular wall damage leads to ventricular dysfunction [ 10 ] characterized by a dilated left ventricle, a thin left ventricular wall, a disrupted myofibrillary architecture, and contractile dysfunction [ 33 , 35 , 36 ]. Ventricular dysfunction in alcoholics is also caused by the disruption of calcium ion homeostasis and its regulation by inhibiting endothelial nitric oxide synthase (eNOS) [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, long-term cAMP overload may induce myofilament calcium desensitization of the cardiac myocytes through increased protein kinase A. Therefore, the desensitized cardiac myocytes cannot respond effectively to the increased calcium influx to enhance the cardiac contractibility when the fluid load increases 21,22 . Secondly, long-term Ca 2+ overload may have a negative impact on the compliance of the heart due to the hypertrophied myocytes and increased myocardial contractility 23 .…”
Section: Discussionmentioning
confidence: 99%